Faktor yang Memengaruhi Kejadian Hiperemesis Gravidarum pada Ibu Hamil Trimester I - Satrimi, Satrimi; Yannti, Yuli; Sinaga, Ribur; Bakara, Sri Muliana Putri (Window of Midwifery Journal, 2025)
Hyperemesis Gravidarum is a condition in pregnant women characterized by nausea and vomiting throughout the day during pregnancy, often occurring in the first trimester. Several factors can lead to hyperemesis gravidarum in pregnant women, including hormonal imbalances involving HCG, estrogen, progesterone, and cortisol. Hyperemesis can be caused by multifactorial issues, including primigravida, allergies, the relationship between psychological factors such as family support, anxiety about pregnancy, and the mother's nutritional status. This study aims to identify the factors influencing the incidence of hyperemesis gravidarum in first-trimester pregnant women. This cross-sectional study was conducted on 68 first-trimester pregnant women in the Working Area of the Ketapang Nusantara Health Center in Central Aceh Regency from October 2021 to March 2022. The sampling technique used was purposive sampling. Data analysis was performed using the Chi-Square test, and the results showed a relationship between knowledge and the incidence of hyperemesis gravidarum (p=0.005), education level (p=0.005), parity (p=0.002), and age during pregnancy (p=0.015). Therefore, pregnant women need to receive health information education about their pregnancy to manage and reduce the morbidity rates in mothers and babies and to address hyperemesis gravidarum during pregnancy.